(untitled) (Confluenţe Bibliologice, 2020)
In this paper the author presents the Map of Dacia, which is part of the historical section of the work Theatrum Orbis Terrarum (World Theater) written by Abraham Ortelius (1527-1598), the Dutch cartographer. Ortelius’s Theatrum Orbis Terrarum (Theatre of the World) is considered the ﬁrst true atlas in the modern sense: a collection of uniform map sheets and sustaining text bound to form a book for which copper printing plates were speciﬁcally engraved. The Ortelius atlas is sometimes referred to as the summary of sixteenth-century cartography. Many of his atlas’s maps were based upon sources that no longer exist or are extremely rare. Moreover, in 1596, Ortelius added a historical section to his atlas, which later became an integral part of the atlas.